Fostering Reading Interest in Grade 3: Indonesian Elementary School Insights: Meningkatkan Minat Baca di Kelas 3: Temuan Sekolah Dasar di Indonesia - Firdasari, Khurin; Astuti, Ruli (Indonesian Journal of Education Methods Development, 2023)
This qualitative study with a phenomenological approach investigates the efforts of a school library in increasing reading interest among grade 3 students at Banjartanggul Elementary School in Indonesia. The research aims to identify effective strategies employed by the library and analyze the factors that hinder students' reading interest. Data was collected through observation, interviews, and documentation. The findings reveal that the school library has optimally fulfilled its role in fostering reading interest, employing strategies such as incentivizing library visits, engaging parents, motivating students, scheduling visits, and expanding book collections. The results offer valuable insights for educators, librarians, and policymakers seeking to enhance reading engagement among young learners. Highlights: Efforts to foster reading interest: The study explores the initiatives taken by the school library to enhance reading interest among grade 3 students. Identification of barriers: The research identifies the factors that hinder reading interest among grade 3 students in the Indonesian elementary school context. Insights for educators and policymakers: The findings offer valuable insights for educators, librarians, and policymakers seeking to promote reading engagement among young learners. Keywords: Reading interest, Grade 3 students, Library initiatives, Barriers, Indonesian elementary school.